Body Adiposity and Endocrine Profile of Female Wistar Rats of Distinct Ages that were Early Weaned - Pietrobon, Carla Bruna; Bertasso, Iala Milene; Silva, Beatrix S.; Peixoto-Silva, Nayara; Oliveira, Elaine; Moura, Egberto Gaspar; Lisboa, Patricia Cristina (Hormone and Metabolic Research, 2020)
Early weaning (EW) is a risk factor for metabolic syndrome. Male rats that were precociously weaned present neonatal malnutrition and, in adulthood, developed overweight, accumulation of body fat, dyslipidemia, changes in glycemic homeostasis, hyperleptinemia, and increase of vitamin D. As metabolic profile of early-weaned females is not known, we investigated the endocrine-metabolic parameters in adolescence and adult female rats of 2 different EW models. Wistar lactating rats and pups from both sexes were separated into 3 groups: non-pharmacological EW (NPEW), dams were involved with a bandage interrupting suckling in the last 3 days of lactation; pharmacological EW (PEW), dams were bromocriptine-treated (0.5 mg/twice a day via intraperitoneal injection) for 3 days before weaning; and control, dams whose pups ate milk throughout lactation. At 21 days-old, NPEW and PEW females had lower body weight. At 180 days-old, NPEW and PEW females showed higher feed efficiency, weight gain, body fat percentage, and greater accumulation of gonadal and retroperitoneal fat depots associated with adipocyte hypertrophy. NPEW females also showed hyperphagia. Only NPEW females presented hyperleptinemia. Plasma thyroid hormones and vitamin D were unchanged among EW females. Regarding sex hormones, at 45 days-old, no change was found in EW females, while at 180 days-old, PEW females had hypoestrogenemia. EW increases the risk for obesity in female rats in adulthood, as already demonstrated for males, although through distinct mechanisms involving some hormones.
Keywords: developmental plasticity; fat mass; leptin; vitamin D; thyroid hormones